Syenite rock as an alternative for potassium source: Synchrotron based investigation and element release kinetics - Amine EL Messbahi; Abdellatif Elghali; Otmane Raji; James J. Dynes; Mohsen Shakouri; Adam F.G. Leontowich; Muhammad Ouabid; Mostafa Benzaazoua (Minerals Engineering, 2026)

Proteome conserved multi-epitope-based vaccine construct against Nipah virus - Taimoor Khan; Tayyab Ali; Muhammad Suhaib Qudus; Gadallah Mohamed; Farukh S. Sharopov; Adam Junka; Yanfang Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Evaluating the effect of Iron biofortification on nutraceutical and aromatic profiles of cereal grains: A case study of pearl millet - Hamza M.A. Abaker; Sulafa B.H. Hashim; Haroon Elrasheid Tahir; Muhammad Arslan; Gustav Komla Mahunu; Zhuhai Li; Xiaodong Zhai; Abdalbasit Adam Mariod; Mohammad Rezaul Islam Shishir; Magdi Ali Osman Mohammed; Ahmed Gaafar Mohammed Elgorashi; Alaa K.M. Khogly; et al. (Food Chemistry, 2026)

The evolution of stone flaking technology at Leang Panninge (South Sulawesi, Indonesia) from the Late Pleistocene to the ‘Toalean’ technocomplex - Suryatman; Akin Duli; David McGahan; Andi Muh. Saiful; Basran Burhan; Ratno Sardi; Zubair Mas’ud; Fardi Ali Syahdar; Muh. Alif; Muhammad Nur; Aisyah Arung Qalam; Iwan Sumantri; et al. (Archaeological and Anthropological Sciences, 2026)

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Unlocking the biomedical potential of coffee pulp: Extraction methodologies and mechanistic insights of non-bean derivatives for health - Munasir; Syaiful Adam Maulana; Rizqi Aulia Nurlaili; Nuhaa Faaizatunnisa; Muhammad Naufal Ariesta; Gusti Nur Aida Fasha; Slamet Widiyanto (Bioresource Technology Reports, 2026)

Safety and tolerability of the ACE-inhibitor lisinopril among Nigerian adults with HIV: preliminary pilot data from a randomized clinical trial - Faisal S. Dankishiya; Hamza Muhammad; Usman J. Wudil; Baba M. Musa; Liping Du; Ibrahim A. Adam; Aima A. Ahonkhai; Anna M. Burgner; Aishatu M. Nalado; Mahmoud U. Sani; Aliyu Abdu; Bryan E. Shepherd; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

High yield low temperature biocompatible activation of biochar for sustainable supercapacitors - Kanwar Muhammad Adam; Chirag Mevada; Vijay Singh Parihar; Amit Tewari; Hamed Pourkheirollah; Jari Keskinen; Matti Mäntysalo (Biomass and Bioenergy, 2026)

Occurrence analysis of alpha-mangostin from different organs of Garcinia mangostana L. - Nurin Syamimi Ahmad Izuren Shah; Mohd Rushdi Abu Bakar; Muhammad Taher; Wan Hazman Danial; Fatmawati Adam; Syarifah Abdul Rahim (Natural Product Research, 2026)

Genomic characterization of Burkholderia glumae K6 and B. gladioli UPMBG7: causal agents of bacterial panicle blight in Malaysia - Adam Zafdri Md Zali; Siti Izera Ismail; Norsazilawati Saad; Muhammad Asyraf Md Hatta; Mohd Razi Ismail; Mohd Termizi Yusof; Mansor Hakiman; Syari Jamian; Sumaiyah Abdullah; Dzarifah Zulperi (European Journal of Plant Pathology, 2026)
Bacterial panicle blight (BPB), caused by Burkholderia glumae and B. gladioli , is a major threat to rice in Malaysia, with potential yield losses up to 75%. In June 2021, BPB symptoms were detected in Kedah rice fields. Isolates were identified through phenotypic traits, pathogenicity tests, and molecular analysis (16S rRNA and gyrB sequencing). Whole-genome sequencing of B. glumae K6 and B. gladioli UPMBG7 was performed using the Illumina NovaSeq 6000 platform. The assembled draft genome of B. glumae K6 contained 210 contigs, with a total genome size of 6.57 Mbp, 68.33% G + C content, and 5,641 coding sequences (CDS). It harbored toxoflavin biosynthesis genes ( toxABCDE , toxJ ) and a Type III secretion system (T3SS), contributing to its pathogenicity. B. gladioli UPMBG7 contained 124 contigs, with a total genome size of 8.22 Mbp, G + C content of 67.99, and 7,022 coding proteins. B. gladioli lacked the toxI gene for toxoflavin production but compensated with pyoverdine siderophore genes ( pvdA ), which facilitate iron acquisition. These findings highlight divergent infection mechanisms, with B. glumae relying on toxoflavin-mediated virulence and B. gladioli on resource competition. The genomic insights support the development of resistant rice cultivars, biological controls, and molecular diagnostics to improve BPB management in Malaysia.

Effect of a GnRH antagonist on the fate of the dominant ovarian follicle and the emergence of the next follicular wave in alpacas - Jaswant Singh; Miruna Munteanu; Muhammad A. Shakeel; Gregg P. Adams (Theriogenology, 2026)

Integrating Molecular and Ecological Insights for better understanding of Bioremediation Potential of Indigenous Fungal Isolates from the Marble Wastewater - Zeeshan Ahmad; Shujaul Mulk Khan; Adam Khan; Muhammad Ishtiaq Ali; Gulnar Tulindinova; Shahab Ali; Jie Yang (Water, Air, & Soil Pollution, 2026)

Integrating nature-inspired optimization techniques and machine learning for accurate CO2/brine interfacial tension estimation: Implications for CO2 sequestration and uncertainty analysis - Joshua Nsiah Turkson; Muhammad Aslam Md Yusof; John Oluwadamilola Olutoki; Bennet Nii Tackie-Otoo; Caspar Daniel Adenutsi; Ingebret Fjelde; Yen Adams Sokama-Neuyam; Victor Darkwah-Owusu (Gas Science and Engineering, 2026)

Intensification of plasma process for the decomposition of p-xylene as a tar model compound to minimize the unwanted byproduct formation - Faisal Saleem; Muhammad Farooq; Azam Saeed; Shehzad Mustafa; Zaeem Bin Babar; Abdul Rehman; Syed Waqas Ahmad; Kui zhang; Adam Harvey (Fuel, 2026)

Performance and nutrient digestibility of broilers fed barley-based diets supplemented with amylase - Lucas S. Bassi; Khaled Itani; Muhammad Ahmad; Adam Smith; Aaron Cowieson; Sebastian Kaczmarek; Birger Svihus (Animal Feed Science and Technology, 2025)

Harnessing the constrained macrocyclic peptide frameworks for the development of antimicrobial peptides to treat infections - Taj Muhammad; Sunithi Gunasekera; John Kerr White; Adam A. Strömstedt; Soumitra Mohanty; Anna Blasi-Romero; Carlos Palo-Nieto; Natalia Ferraz; Annelie Brauner; Ulf Göransson (Phytochemistry Letters, 2025)

Roles of Fox gene in the development and reproduction of diamondback moth - Anam Noreen Abbas; Mubashir Tariq; Faisal Munir; Uroosa Zaheer; Ibrahim Adam; Muhammad Asad; Guang Yang (Journal of Insect Physiology, 2025)

Hydropuntia edulis extract mitigates metabolic dysregulation via DPP-4 inhibition, lipid modulation, and GLP-1/AKT1 pathway activation - Maghfirah Savitri; Trina Ekawati Tallei; Ahmad Akroman Adam; Nur Balqis Maulydia; Fatimawali Fatimawali; Gadis Sabrina Tanjung; Muhammad Firdaus; Rony Abdi Syahputra; Fahrul Nurkolis (Food Bioscience, 2025)

Insights on Diversity and Exploitation of Sharks and Rays in the East Coast of Peninsular Malaysia - Ahmad Shaqiq Alizdi Ahmad Sharikin; Abdullah Mohamad; Muhammad Hanif Fadzli; Wan Mohamad Aiman Wan Azimi; Serena Adam; Aslina Nasir; Rumeaida Mat Piah (Thalassas: An International Journal of Marine Sciences, 2025)

Dispersal of Per- and polyfluoroalkyl substances (PFASs) and toxic metals: a probable influence of inorganic fluoride and ionic strength in the Shiqi River Basin of Nanjing City, South-Eastern China - Muhammad Ibrahim; Yiping Li; Xiaolin Zhu; Yaning Wang; Yan Chunmin; Hafsat Alhassan Danjaji; Abdulhakim Wagini Hassan; Adam Umar Jibo (Clean Technologies and Environmental Policy, 2025)

Assessing changes between two years in macrobenthic invertebrate communities in four sub-tropical Australian estuaries - Muhammad M. Islami; Adam Davey; Stephen D.A. Smith; Victoria J. Cole; Rachel Przeslawski; Kirsten Benkendorff (Regional Studies in Marine Science, 2025)

Tailored synthesis of heterojunction CuNTiO2 and g-C3N4 composite for advanced degradation of 1,2,4-trichlorobenzene under visible light - Olive Mekontchou Yemele; Zhenhua Zhao; Ervice Ymele; Abduelrahman Adam Omer; Muhammad Usman; Liling Xia; Cedric Karel Fonzeu Monguen; Teng Binglu; Franck Ghislain Emani (Journal of Water Process Engineering, 2025)

Harmonizing soil carbon simulation models, emission factors and direct measurements used in LCA of agricultural systems - Simone Pelaracci; Pietro Goglio; Simon Moakes; Marie Trydeman Knudsen; Klara Van Mierlo; Nina Adams; Fossey Maxime; Alberto Maresca; Manuel Romero-Huelva; Muhammad Ahmed Waqas; Laurence G. Smith; Frank Willem Oudshoorn; et al. (Agricultural Systems, 2025)

Safeguarding tourism economies: Managing the financial and ecological challenges of oil spills on coastal destinations - Arif Jameel; Muhammad Imran; Nawal Abdullah Adam; Sanjar Mirzaliev; Marguba Khidirov; Gao Yingying (Marine Pollution Bulletin, 2025)

Enhancing the resilience of intercropping systems to changing moisture conditions in Africa through the integration of grain legumes: A meta-analysis - Adam Muhammad Adam; Ken E. Giller; Leonard Rusinamhodzi; Frank Rasche; Eric Koomson; Carsten Marohn; Georg Cadisch (Field Crops Research, 2025)

Quantifying non-target seahorse fisheries and domestic traditional medicine-based trade in Malaysia - Reana May Yen Ng; Adam Chee Ooi Lim; Chin Nurhiqwanalina Binti Henry Chin Siew Lee; Norazliana Binti Abdul Majib; Muhammad Ali Syed Hussein; Amy Yee-Hui Then (Fisheries Research, 2025)

Characterization and identification of the key volatile and non-volatile substances of Vangueria madagascariensis J.F. Gmel fruits (Kirkir) and exploration of their binding interactions with olfactory and taste receptors using computational chemistry methodology - Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Mohammad Rezaul Islam Shishir; Li Zhihua; Suliman Khan; Abdalbasit Adam Mariod; Hamza A.M. Abaker; Howida Elkheir Ibrahim; Hesham R. El-Seedi; Zou Xiaobo (Food Chemistry, 2024)

Microplastics Contamination in Environment and Marine Animals at Kodek Bay, Lombok, Indonesia - Moh. Awaludin Adam; Husna Shofi Talbia; Dwi Ariyanti; Sonny Kristianto; Nadda Khalila Chairunnisa; Maya Aprilia; Muhammad Firdaus; Ramli Marzuki; Aditya Prana Iswara; Wisnu Prayogo; Tuti Mutia; Heni Masruroh (Water, Air, & Soil Pollution, 2024)

Improving Short-term Daily Streamflow Forecasting Using an Autoencoder Based CNN-LSTM Model - Umar Muhammad Mustapha Kumshe; Zakariya Muhammad Abdulhamid; Baba Ahmad Mala; Tasiu Muazu; Abdullahi Uwaisu Muhammad; Ousmane Sangary; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Mosaad Ali Hussein Ali; Aliyu Uthman Bello; Muhammad Muhammad Bala (Water Resources Management, 2024)

Correction to: Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Eco-toxicological impacts of industrial wastewater and the role of bio-electrochemical systems (BES) in remediation: a review - Muhammad Usman; Zhenhua Zhao; Olive Mekontchou Yemele; Muhammad Ibrahim; Waleed Raza; Zia Ur Rehman; Abduelrahman Adam Omer; Mir Moazzam Ali Talpur; Mouna Jeridi; Ghulam Abbas Ashraf; Hafsat Alhassan Danjaji (Clean Technologies and Environmental Policy, 2024)

Analyzing Agricultural Land Use with Cellular Automata-MARCOV and Forecasting Future Marine Water Quality Index: A Case Study in East Coast Peninsular Malaysia - Mohd Saiful Samsudin; Azman Azid; Muhammad Amar Zaudi; Mohd Ridhwan Adam; Muhamad Shirwan Abdullah Sani; Shazlyn Millenana Saharuddin; Aminu Ibrahim; Mohd Fahmi Mohd Nasir; Mou Leong Tan; Nurul Izzati Mohd Ali (Water, Air, & Soil Pollution, 2024)

Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Harmonizing methods to account for soil nitrous oxide emissions in Life Cycle Assessment of agricultural systems - Pietro Goglio; Simon Moakes; Marie Trydeman Knudsen; Klara Van Mierlo; Nina Adams; Fossey Maxime; Alberto Maresca; Manuel Romero-Huelva; Muhammad Ahmed Waqas; Laurence G. Smith; Giampiero Grossi; Ward Smith; et al. (Agricultural Systems, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Morphological and molecular characterisation of Cymothoa eremita (Brunnich, 1783) (Isopoda: Cymothoidae) from the South China Sea - Melissa Beata Martin; Muhammad Adam Mohamed Yusoff; Noor Syazwaney Hashim; Thinh Dinh Do; Nakisah Mat Amin; Faizah Shaharom-Harrison; Yeong Yik Sung; Wang Min; Liang Yantao; Md Asaduzzaman; Li Lian Wong (Regional Studies in Marine Science, 2024)

Effects of agro based organic amendments on growth and cadmium uptake in wheat and rice crops irrigated with raw city effluents: Three years field study - Hiba Shaghaleh; Muhammad Azhar; Muhammad Zia-ur-Rehman; Yousef Alhaj Hamoud; Ammar Ali Adam Hamad; Muhammad Usman; Muhammad Rizwan; Jean Wan Hong Yong; Hesham F. Alharby; Abdullah G. Al-Ghamdi; Basmah M. Alharbi (Environmental Pollution, 2024)

HPLC-DAD, GC–MS, UHPLC-Q-TOF/MS2, ICP-MS and FT-NIR combined with the chemometrics explain seasonal variation in Cassia senna L. leaves from the coast of Red Sea in Sudan - Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Huang Xiaowei; Li Zhihua; Abdalbasit Adam Mariod; Isameldeen I.H. Abdalla; Hesham R. El-Seedi; Ahmed Abdel Aziz Ahmed; Zou Xiaobo (South African Journal of Botany, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

An autoencoder-based stacked LSTM transfer learning model for EC forecasting - Abdullahi Uwaisu Muhammad; Hamza Djigal; Tasiu Muazu; Jibril Muhammad Adam; Abdoul Fatakhou Ba; Umar Sani Dabai; Sani Tijjani; Muhammad Sabo Yahaya; Aliyu Ashiru; Umar Muhammad Mustapha Kumshe; Saddam Aliyu; Faruwa Ajibola Richard (Earth Science Informatics, 2023)

Dinuclear gold(I) complexes based on carbene and diphosphane ligands: bis[2-(dicyclohexylphosphano)ethyl]amine complex inhibits the proteasome activity, decreases stem cell markers and spheroid viability in lung cancer cells - Naike Casagrande; Cinzia Borghese; Giuseppe Corona; Donatella Aldinucci; Muhammad Altaf; Adam A. A. Sulaiman; Anvarhusein A. Isab; Saeed Ahmad; Abdul Malik P. Peedikakkal (JBIC Journal of Biological Inorganic Chemistry, 2023)

Beyond the aging spine – a systematic review of functional changes in the human brain in cervical spondylotic myelopathy - Ali Fahim Khan; Fauziyya Muhammad; Esmaeil Mohammadi; Christen O’Neal; Grace Haynes; Sanaa Hameed; Brynden Walker; Michael L. Rohan; Andriy Yabluchanskiy; Zachary Adam Smith (GeroScience, 2023)

The Western Himalayan fir tree ring record of soil moisture in Pakistan since 1855 - Zahid Rauf; Nowsherwan Zarif; Adam Khan; Samina Siddiqui; Seerat Fatima; Wahiba Iqbal; Hira Amin; Tahir Iqbal; Muhammad Arif; Shehla Sattar; Muhammad Tahir Rauf (International Journal of Biometeorology, 2023)

Transport and depositional processes of organic matter evaluated by biomarker profiles in Miocene turbiditic sequences from Hokkaido, Japan - Muhammad Adam Ismail; Hiroyasu Asahi; Ken Sawada (Sedimentary Geology, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Classification of Black Mahlab seeds (Monechma ciliatum) using GC–MS and FT-NIR and simultaneous prediction of their major volatile compounds using chemometrics - Haroon Elrasheid Tahir; Abdalbasit Adam Mariod; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Huang Xiaowei; Li Zhihua; Isameldeen I.H. Abdalla; Zou Xiaobo (Food Chemistry, 2023)

Seasonal variability of Total Suspended Sediment off the Banjir Kanal Barat River, Semarang, Indonesia estimated from Sentinel-2 images - Anindya Wirasatriya; Lilik Maslukah; Elis Indrayanti; Muh. Yusuf; Adzkia Pincta Milenia; Alvin Aulia Adam; Muhammad Helmi (Regional Studies in Marine Science, 2023)

Complement C3a Receptor (C3aR) Mediates Vascular Dysfunction, Hippocampal Pathology, and Cognitive Impairment in a Mouse Model of VCID - Kanchan Bhatia; Adam Kindelin; Muhammad Nadeem; Mohammad Badruzzaman Khan; Junxiang Yin; Alberto Fuentes; Karis Miller; Gregory H. Turner; Mark C. Preul; Abdullah S. Ahmad; Elliott J. Mufson; Michael F. Waters; et al. (Translational Stroke Research, 2022)

Sub-acute toxicity study on hydromethanolic leaves extract of Combretum hypopilinum (Combretaceae) Diels in Wistar rats - Mubarak Hussaini Ahmad; Abdulkadir Umar Zezi; Sherifat Bola Anafi; Omar Yahya Alshargi; Mustapha Mohammed; Sagir Mustapha; Auwal Adam Bala; Surajuddeen Muhammad; Sa’adatu Muhammad Julde; Abubakar Sadiq Wada; Abubakar Ibrahim Jatau (Toxicological Research, 2022)

Feasibility Study of Harnessing Low Wind Speed Turbine as Hybrid Power Source for Offshore Platforms - Izleena Md Iqbar; Masdi Muhammad; Syed Ihtsham Ul-Haq Gilani; Frank Adam (Journal of Marine Science and Engineering, 2022)
In this study, the viability of harnessing wind energy for offshore oil and gas (O&G) platforms as a micro-grid solution in low wind speed regions to power O&G platforms is explored. However, wind, as a renewable energy, is known to be highly variable and is unable to provide standalone power reliably within a micro-grid solution due to the variation of the wind speed at hub height, which subsequently leads to a variation of the power outcome. Here, a hybrid power generation concept is developed in which one gas turbine generator (GTG) is replaced with a floating horizontal axis wind turbine (WT) system. By setting up this system, the reduction of the maintenance costs of the GTGs and the reduction of fuel gas consumption reduces carbon dioxide (CO2) emissions. In addition to this, the fuel gas savings in terms of the business side of such a solution provide a positive revenue impact. In this feasibility study, a technical framework is developed, followed by an economic framework. In the technical framework, wind assessments are performed to obtain the annual energy production for the selected field. Furthermore, an economic framework is established for both conventional and hybrid concepts in two scenarios: greenfield and brownfield, where the incremental net present value (NPV) and levelized cost of energy are calculated. The resultant difference in NPV for hybrid power generation compared to conventional power generation was found to be between 22% and 37%. The levelized cost of energy (LCOE) for WT is USD 165.52/MWh, which is 39% lower than for conventional, gas turbine-only operations. The LCOE for the hybrid approach is lower than for the conventional scenario by 22%. In conclusion, the hybrid micro-grid concept solution can harness wind energy from low wind regions with better economic benefits compared to conventional methods through the proper selection of the WT system, its floating substructure, and efficient micro-grid system for powering oil and gas platforms.

A critical review with emphasis on recent pieces of evidence of Moringa oleifera biosorption in water and wastewater treatment - Asmaa Benettayeb; Muhammad Usman; Coffee Calvin Tinashe; Traore Adam; Boumediene Haddou (Environmental Science and Pollution Research, 2022)
The increasing demand for using competent and inexpensive methods based on biomaterials, like adsorption and biosorption, has given rise to the low-priced alternative biosorbents. In the past few years, Moringa oleifera (MO) has emerged as a green and low-priced biosorbent for the treatment of contaminated waters with heavy metals and dyes, and given its availability, we can create another generation of effective biosorbents based on different parts of this plant. In this review paper, we have briefed on the application of MO as a miraculous biosorbent for water purification. Moreover, the primary and cutting-edge methods for the purification and modification of MO to improve its adsorption are discussed. It was found that MO has abundant availability in the regions where it is grown, and simple chemical treatments increase the effectiveness of this plant in the treatment of some toxic contaminants. The different parts of this miraculous plant’s “seeds, leaves, or even husks” in their natural form also possess appreciable sorption capacities, high efficiency for treating low metal concentrations, and rapid adsorption kinetics. Thus, the advantages and disadvantages of different parts of MO as biosorbent, the conditions favorable to this biosorption, also, the proposal of a logical mechanism, which can justify the high efficiency of this plant, are discussed in this review. Finally, several conclusions have been drawn from some important works and which are examined in this review, and future suggestions are proposed.

Short-term dynamics and long-term relationship between natural gas consumption and economic growth in Nigeria: an ARDL approach with breaks - Mukhtar Danladi Galadima; Abubakar Wambai Aminu; Ibrahim Muhammad Adam; Ibrahim Mohammed Adamu; Hassan Hassan Suleiman (Environmental Science and Pollution Research, 2022)

In silico molecular docking and molecular dynamic simulation of potential inhibitors of 3C-like main proteinase (3CLpro) from severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) using selected african medicinal plants - Mustafa Alhaji Isa; Adam Mustapha; Sahar Qazi; Khalid Raza; Ibrahim Alkali Allamin; Muhammad M. Ibrahim; Mohammed M. Mohammed (Advances in Traditional Medicine, 2022)

Propaedeutic Study of Biocomposites Obtained With Natural Fibers for Oceanographic Observing Platforms - Simona Aracri; Marco Contardi; Ilker S. Bayer; Muhammad Zahid; Francesco Giorgio-Serchi; Adam A. Stokes (Frontiers in Marine Science, 2021)
In response to the pervasive anthropogenic pollution of the ocean, this manuscript suggests the use of biodegradable elastomers in marine applications. The present study characterizes 25 samples of highly biodegradable polymers, obtained blending a base elastomer with natural fibers. Mechanical analysis and Scanning Electron Microscope imaging, reveal how base polymers behave differently depending on the plant fiber chosen, on the external forcing—exposure to water—and on the doses that constitute the final biocomposite. Results suggest that Ecoflex TM 00-30 and Ecoflex TM 00-50, mixed with potato starch, perform best mechanically, maintaining up to 70% of their maximum tensile strain. Moreover, early signs of degradation are visible on polysiloxane rubber blended with 50% vegetable fibers after 19 hours in distilled water. Analyses demonstrate that highly biodegradable elastomers are good candidates to satisfy the requirements of aquatic devices. Furthermore, the discussed materials can improve the dexterity and biodegradability of marine technology.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Remote Ischemic Post-Conditioning Therapy is Protective in Mouse Model of Traumatic Optic Neuropathy - Muhammad Nadeem; Adam Kindelin; Laura Mahady; Kanchan Bhatia; Md Nasrul Hoda; Andrew F. Ducruet; Saif Ahmad (NeuroMolecular Medicine, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Controversy over the Mode of Growth of Cambial Cylinder - Adam Miodek; Wiesław Włoch; Muhammad Iqbal; Aldona Gizińska; Paweł Kojs (The Botanical Review, 2021)

Tree-ring-based temperature reconstruction from the western Himalayan region in northern Pakistan since 1705 C.E. - Adam Khan; Moinuddin Ahmed; Narayan Prasad Gaire; Javed Iqbal; Muhammad Faheem Siddiqui; Afsheen Khan; Mohib Shah; Ali Hazrat; Najm Us Saqib; Wali Khan Mashwani; Sher Shah; Sanjaya Bhandari (Arabian Journal of Geosciences, 2021)

In silico predictions on the possible mechanism of action of selected bioactive compounds against breast cancer - Aliyu Muhammad; Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Ibrahim Malami; Ibrahim Babangida Abubakar; Amina Isah kandi; Adam Muntaka Idris; Sabi’u Yusuf; Salihu Muktar Musa; Nagedu Monday; Zak-wan Sidi Umar (In Silico Pharmacology, 2020)

Genetic analyses of native Fusarium head blight resistance in two spring wheat populations identifies QTL near the B1, Ppd-D1, Rht-1, Vrn-1, Fhb1, Fhb2, and Fhb5 loci - Dinushika Thambugala; Anita L. Brûlé-Babel; Barbara A. Blackwell; George Fedak; Adam J. Foster; Dan MacEachern; Jeannie Gilbert; Maria Antonia Henriquez; Richard A. Martin; Brent D. McCallum; Dean Spaner; Muhammad Iqbal; et al. (Theoretical and Applied Genetics, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Vegetation-environment relationship in conifer dominating forests of the mountainous range of Indus Kohistan in northern Pakistan - Adam Khan; Moinuddin Ahmed; Muhammad Faheem Siddiqi; Mohib Shah; Eduardo Soares Calixto; Afsheen Khan; Paras Shah; Javed Iqbal; Muhammad Azeem (Journal of Mountain Science, 2020)

Rainfall reconstruction for the Karakoram region in Pakistan since 1540 CE reveals out‐of‐phase relationship in rainfall between the southern and northern slopes of the Hindukush‐Karakorum‐Western Himalaya region - Adam Khan; Feng Chen; Moinuddin Ahmed; Muhammad Usama Zafar (International Journal of Climatology, 2020)
Climate change has influenced the glaciers and water resources in the Hindukush‐Karakorum‐Himalaya region. The relatively short instrumental record of northern Pakistan makes long‐term climate change assessments difficult. In this paper, tree‐ring width chronologies were developed from two stands of spruce species ( Picea smithiana ) in the Karakoram region of northern Pakistan. The results of the correlation analysis revealed that tree‐ring growth of spruce was limited by annual (June–May) precipitation. Based on the regional chronology, we developed an annual precipitation reconstruction for the period 1540–2016 CE. The precipitation reconstruction equation accounts for 40% of the regional precipitation variance during the instrumental period 1946–2016. Dry episodes with rainfall below the 477‐year average occurred from 1569 to 1577, 1598 to 1612, 1621 to 1621, 1638 to 1654, 1673 to 1680, 1697 to 1720, 1728 to 1739, 1753 to 1761, 1777 to 1793, 1801 to 1840, 1860 to 1874, 1914 to 1932, 1960 to 1985, 1998 to 2011. Wet episodes occurred from 1540 to 1568, 1578 to 1597, 1613 to 1620, 1632 to 1637, 1655 to 1672, 1681 to 1696, 1721 to 1727, 1740 to 1752, 1762 to 1776, 1794 to 1800, 1841 to 1859, 1875 to 1913, 1933 to 1959, 1986 to 1997. Furthermore, the results of spatial correlation analyses show that the reconstructed precipitation represents the regional precipitation variations for northern Pakistan and nearby high‐altitude mountains. The out‐of‐phase relationship in tree‐ring records of the Karakoram region and surrounding areas suggests that the Karakoram was under the control of large‐scale ocean–atmosphere–land circulations on a decadal timescale in the past centuries. In addition, by the comparison between the precipitation reconstruction and the instrumental data, we found that the drought risk of Karakoram has increased in the past 70 years and that extreme events are likely to become more severe and more frequent under the backdrop of climatic warming.

Chronic treatment with a metabotropic mGlu2/3 receptor agonist diminishes behavioral response to a phenethylamine hallucinogen - Adam L. Halberstadt; Jochem V. F. van der Zee; Muhammad Chatha; Mark A. Geyer; Susan B. Powell (Psychopharmacology, 2019)

Correction to: Pharmacological characterization of the LSD analog N-ethyl-N-cyclopropyl lysergamide (ECPLA) - Adam L. Halberstadt; Landon M. Klein; Muhammad Chatha; Laura B. Valenzuela; Alexander Stratford; Jason Wallach; David E. Nichols; Simon D. Brandt (Psychopharmacology, 2019)

Pharmacological characterization of the LSD analog N-ethyl-N-cyclopropyl lysergamide (ECPLA) - Adam L. Halberstadt; Landon M. Klein; Muhammad Chatha; Laura B. Valenzuela; Alexander Stratford; Jason Wallach; David E. Nichols; Simon D. Brandt (Psychopharmacology, 2019)

Description of Goussia kuehae n. sp. (Apicomplexa: Eimeriidae) infecting the Asian seabass, Lates calcarifer (Bloch) (Perciformes: Latidae), cultured in Malaysian fish farms - Csaba Székely; Muhammad Hafiz Borkhanuddin; Faizah Shaharom; Mohd Shukri Adam Embong; Kálmán Molnár (Systematic Parasitology, 2013)

Genetic and linkage analysis of familial congenital hypothyroidism: exclusion of linkage to the TSH receptor gene - B. Edman Ahlbom; Muhammad Yaqoob; Agne Larsson; Adam Ilicki; Göran Annerén; C. Wadelius (Human Genetics, 1997)